Transformation of Nursing Human Resources Based on Strategy: Addressing the Challenges of Value-Based Care in Modern Hospitals in Indonesia - Rio Verdiansyah; Ratna Meilina; Sitta Diani Fichara; Baskoro Abdiansyah; Margareta Susilowati; Rista Tri Wulandari; Rr. Tutik Sri Hariyati; Hanny Handiyani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Strategic planning and management of human resources (HR) play a crucial role in improving the quality of hospital services. This field study aims to analyze human resource development strategies, particularly in nursing, at Hospital. Field study method. Data were collected through interviews at Hospital X and documentation from Hospital X. Data were obtained through group-based analysis of academic documents and assessment of the hospital's existing conditions. The analysis revealed that Hospital X's main strengths lie in HR competencies, recruitment systems, and ongoing training programs. However, it faces challenges in work culture and career development systems. The proposed strategies include digitalizing HR management systems, collaborating with educational institutions to strengthen nursing capacity, and fostering a culture of patient safety. As part of the implementation, a five-year work plan was developed, encompassing CPD training programs, the development of a Human Resources Information System (HRIS), and the enhancement of reward and recognition programs. This strategic approach is expected to enhance the efficiency, productivity, and competitiveness of hospital human resources amid the transformation of healthcare services.